Problematika Etis Pernikahan Monogami: Praktik Poligami dalam Perjanjian Lama dan Keluarga Kristen Era Post-Modernism - Kezia Siwalette, Michelle; Olly Tuegeh, Novalyn; Valent Nainggolan, Rahmat; Hia, Eka Permata Sari (SAINT PAUL'S REVIEW, 2023)
Monogamous marriage in the Christian context is a sacred institution emphasized by God's teachings since the beginning of human creation. However, in reality, the practice of polygamous marriages is rooted in history, and has even been passed down from generation to generation in the Old Testament and contemporary Christians. This research adopts a qualitative method with a case study approach to the practice of polygamous marriages carried out by Biblical figures, through text exegesis that reveals views on the pros and cons of polygamous marriages. This research study shows that the implementation of polygamous marriages in the Old Testament was caused by several factors such as: the existence of social customs and laws at that time, transactional marriages, and the presence of additional wives as a result of local culture. However, based on Bible analysis, God never approves of polygamy. Thus, it is hoped that this research can provide understanding to the Christian Society of the Post-Modernism era.